Brassica Recent Advances - Kumar, Sarwan (IntechOpen, 2023)
Brassica crops, including broccoli, cauliflower, cabbage, and mustard, are among the most important crops worldwide with oilseed Brassica among the largest traded agricultural commodities. They play a vital role in agriculture, horticulture, and human nutrition. The health-promoting and disease-preventing properties of Brassica vegetables are well documented, and their nutritional value makes them an essential part of a balanced diet. Brassica - Recent Advances provides a comprehensive overview of the recent research on Brassica crops. The book covers such topics as the breeding of Brassica crops, agronomic practices, pest management, and plant secondary metabolites. It is an essential resource for researchers, students, and professionals interested in Brassica crops and their applications.